Social Status of Physical Education, Sport, and Health (PJOK) Teachers of Senior High Schools in Semarang - Prasetyo, Isnaeni Agung; Rahayu, Tandiyo; Rustiana, Eunike Raffy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the occupational prestige, occupational status, and the self-esteem of the PJOK teachers in Semarang in terms of the teacher's perspective. The method used in this research was quantitative descriptive. The research sample was 123 respondents of PJOK teachers of all senior high schools in Semarang. The results obtained were that the teaching profession was considered by the respondents as an occupation that had very high prestige. PJOK teachers regarded their occupational status highly, despite the fact that 4% of teachers considered their occupational status to be low. PJOK teachers had very high self-esteem, even though there were 2% of PJOK teachers who had low self-esteem. It was suggested for teachers to improve their competence and self-esteem as a study to improve the quality of physical education learning.